Indirect contact matters: Mid-flight external trunk perturbation increased unilateral anterior cruciate ligament loading variables during jump-landings - Song, Y.; Li, L.; Layer, J.; Fairbanks, R.; Jenkins, M.; Hughes, G.; Smith, D.; Wilson, M.; Zhu, Q.; Dai, B. (Journal of Sport and Health Science, 2023)
Purpose To determine the effect of unanticipated mid-flight medial-lateral external perturbation of the upper or lower trunk on anterior cruciate ligament (ACL) loading variables during jump-landings.